Empowering employees with spiritual intelligence for higher quality food-hygiene practices and food service performance of on-premise caterers - Saad, Mazni; Husain, Rosita; Abdul Rani, Anita; Abdul Ghani, Airin (Institute of Physics Publishing, 2019)
Empowering employees’ spiritual intelligence (SQ) is about bringing back the soul of the hospitality business. This study intends to identify factors that affect a food handler’s’ SQ and also to discover SQ’s potential role in mediating food-hygiene practices and foodservice performance. Using judgemental sampling, this study conducted a cross-sectional study to analyse usable data of 1026. The results show that demographic factors significantly affect SQ level. Food-hygiene practices and food service performance were fully mediated by SQ, thus supporting the food handlers’ thoughts of self-development and success at work. It is proposed that the positive outcomes from the large and varied datasets of the model can be generalised to the routine practices and performance of other institutions.